2012
DOI: 10.3390/atmos3010103
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Modeled Plume Injection Height with Satellite-Derived Observed Plume Height

Abstract: Plume injection height influences plume transport characteristics, such as range and potential for dilution. We evaluated plume injection height from a predictive wildland fire smoke transport model over the contiguous United States (U.S.) from 2006 to 2008 using satellite-derived information, including plume top heights from the Multi-angle Imaging SpectroRadiometer (MISR) Plume Height Climatology Project and aerosol vertical profiles from the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP). While s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 36 publications
(42 reference statements)
2
41
0
Order By: Relevance
“…fed.us/pnw/fera/feps/index.shtml), which complements them with a comprehensive fire description. However, evaluation of the system performance against MISR by Raffuse et al (2012) confirmed limited applicability of Briggs formulations to wildland fires, in agreement with conclusions of Sofiev et al (2012). An evaluation and some improvements of the technique were suggested by Stein et al (2009) based on dispersion modelling of a few plumes.…”
Section: Introductionsupporting
confidence: 69%
“…fed.us/pnw/fera/feps/index.shtml), which complements them with a comprehensive fire description. However, evaluation of the system performance against MISR by Raffuse et al (2012) confirmed limited applicability of Briggs formulations to wildland fires, in agreement with conclusions of Sofiev et al (2012). An evaluation and some improvements of the technique were suggested by Stein et al (2009) based on dispersion modelling of a few plumes.…”
Section: Introductionsupporting
confidence: 69%
“…However, this "thermal" approach is numerically cost consuming and difficult to use, being very sensitive to the chosen input parameters. Finally, some vertical profiles are close to the vertical diffusivity profile (K z ) shape with the maximum of injection at the height H p /2, such as in Raffuse et al (2012) and Veira et al (2015).…”
Section: The Vertical Profile Of Biomass Burning Aerosol Emissionsmentioning
confidence: 65%
“…When used with wildfires, they generally fail to predict large fire impact, certainly because of their weak representation of microphysical processes (Achtemeier et al, 2011) which affect the simulation of PyroCu and PyroCb plumes. For example, using the Briggs equation and the CMAQ model to simulate fires emission in the USA between 2006 and 2008, Raffuse et al (2012) show that most of their plumes where below the level expected from remote-sensing measurement. At present, three parameterizations of plume rise model stand out of the literature, namely Freitas et al (2007), Rio et al (2010), and Sofiev et al (2012).…”
Section: Injh Models Descriptionmentioning
confidence: 99%